Selectivity of Monaural Synaptic Inputs Underlying Binaural Auditory Information Integration in the Central Nucleus of Inferior Colliculus - Wei, Jinxing; Zhong, Wen; Xiao, Cuiyu; Liu, Yun; Song, Changbao; Xiao, Zhongju (Frontiers in Cellular Neuroscience, 2018)
Neurons in the central nucleus of the inferior colliculus (ICC) receive ascending inputs from the ipsi- and contra-lateral auditory pathway. However, the contributions of excitatory or inhibitory synaptic inputs evoked by ipsi- and contralateral stimuli to auditory responses of ICC neurons remain unclear. Using in vivo whole-cell voltage-clamp recordings, we investigated excitatory and inhibitory synaptic currents in neurons of the ICC in response to binaural stimulation by performing an intensity-intensity scan. To systematically analyze the contribution of the ipsi- and contralateral ear, the sound intensity was randomly delivered to each side from 0 to 70 dB SPL. Although the synaptic responses were dominated by contralateral inputs at weak sound intensities, they could be increased (or decreased) by additional ipsilateral stimulation at higher intensities. Interestingly, the synaptic responses to contralateral acoustic inputs were not linearly superimposed with ipsilateral ones. By contrast, the responses showed either a contralateral or ipsilateral profile, dependent on which one was more dominant. This change occurred at a certain intensity “switch” point. Thus, the binaural auditory responses of the ICC neurons were not simply mediated by the summation of the inputs evoked by ipsi- and contra-lateral stimulation. This suggests that the ICC might inherit the acoustic information integrated at the brainstem, causing the selectivity of monaural excitation and inhibition to underlie the neuronal binaural acoustic response.